Improvement in Frailty in a Patient With Severe Chronic Obstructive Pulmonary Disease After Ninjin'yoeito Therapy: A Case Report - Kuniaki, Hirai; Akihiko, Tanaka; Tetsuya, Homma; Hatsuko, Mikuni; Tomoko, Kawahara; Shin, Ohta; Sojiro, Kusumoto; Mayumi, Yamamoto; Fumihiro, Yamaguchi; Shintaro, Suzuki; Tsukasa, Ohnishi; Hironori, Sagara (Frontiers in Nutrition, 2018)
Frailty is a poor prognostic factor in patients with chronic obstructive pulmonary disease (COPD), and although various studies have assessed the effects of conventional treatment with bronchodilators, nutritional support, and pulmonary rehabilitation for frailty in patients with COPD, none have addressed the effects of traditional Japanese medicine (Kampo medicine). Herein, we report successful management of frailty using Ninjin'yoeito therapy in a 76-year-old patient with COPD. Despite being prescribed multiple bronchodilators, nutritional supplement therapy, patient education, and pulmonary rehabilitation, the patient exhibited unintentional weight loss, low energy, and low physical activity. Ninjin'yoeito was prescribed and these subjective symptoms began to improve at 1 month after treatment initiation. At 6 months, the patient reported no frailty, had increased muscle mass, and had achieved an almost normal healthy state. Ninjin'yoeito has been associated with both physical effects, such as improvement in overall physical strength and appetite, and reduction in fatigue, apart from psychological effects, such as greater motivation and reduction of depression and anxiety symptom. Physicians have usually treated COPD primarily with organ-specific treatments, such as bronchodilators; however, addressing both physiological and psychological vulnerability has been difficult. This case report illustrates the potential usefulness of Ninjin'yoeito treatment for frailty in patients with COPD.